Business in the Work and World of David Foster Wallace. (April 2016) - Michaelson, Christopher
Arguably, no author, scholar, or other commentator has depicted the condition of turn-of-the-century American capitalism as entertainingly and insightfully as David Foster Wallace. His central concern was the allure of the gifts of commercial production and the unwitting complicity of both producers and consumers in perpetuating entertainment at the expense of the examined life. This article uses ethical criticism and literary critical theory to explore the subjective experience of business in Wallace's work, in correspondence with scholarship on institutional theory and marketing ethics, to point toward normative conclusions about how, in Wallace's words, to live consciously.